Advances in the application and research of steel bridge deck pavement. (November 2022) - Liu, Yongjian; Shen, Zhenlong; Liu, Jiang; Chen, Sha; Wang, Jianping; Wang, Xiaolong
Abstract: The common diseases of orthotropic steel deck pavement have seriously affected the service life and safe operation of long-span steel bridges. This paper presents an overview on current application and research status of steel bridge deck pavement. Comparations were made on the design requirements of steel bridge deck pavement in several specifications of China, USA, and Japan. The pavement structures, deck stiffnesses and corresponding environmental temperatures were collected from 119 steel bridges around the world. Based on the information collected, the material performance, combination mechanism, technical characteristics and application prospects of various pavement structures were analyzed. Finally, comparison was made on different calculation methods of bridge deck stiffness. Results show that double-layer EAM, GAM + SMAM and ERS are the most commonly used pavement structures of steel deck presently. However, for most of application cases, the actual life cannot reach the design service life of 15 years. Rigid base can significantly improve the stress condition of surface pavement and steel top plate. However, the calculation method is not clear for whether regards the rigid base as a permanent structure or a pavement structure, which cause significant different results in the stiffness calculation of steel bridge deck. In the future, the improvement of the service life of steel deck pavement should focus on improving the uneven distribution of bridge deck stiffness and developing new and efficient pavement structures.